2021
DOI: 10.3390/cancers13112810
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Signals from Gut Microbiota: Perspectives for Brain Glioma

Abstract: Glioblastoma (GBM) is the most aggressive form of glioma tumor in adult brain. Among the numerous factors responsible for GBM cell proliferation and invasion, neurotransmitters such as dopamine, serotonin and glutamate can play key roles. Studies performed in mice housed in germ-free (GF) conditions demonstrated the relevance of the gut-brain axis in a number of physiological and pathological conditions. The gut–brain communication is made possible by vagal/nervous and blood/lymphatic routes and pave the way f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 203 publications
0
22
0
Order By: Relevance
“…Metabolites formed by the microbiome can produce epigenetic changes (57). Recent investigations are disclosing intriguing circuits that involve neurotransmitters produced by the gut microbiome with an effect on cells at a different stage of differentiation (58).…”
Section: Gut Microbiome Gut-brain Axis and Kd: A Broadband Connection Still To Explorementioning
confidence: 99%
“…Metabolites formed by the microbiome can produce epigenetic changes (57). Recent investigations are disclosing intriguing circuits that involve neurotransmitters produced by the gut microbiome with an effect on cells at a different stage of differentiation (58).…”
Section: Gut Microbiome Gut-brain Axis and Kd: A Broadband Connection Still To Explorementioning
confidence: 99%
“… 15 In addition, a recent study by D’Alessandro et al 16 showed that glioma-bearing mice treated with antibiotics have increased tumor growth, changes in natural killer cells, and changes in microglia phenotype. 16 , 73 Altogether, these studies demonstrate the interplay between the gut–brain axis in glioma mice models and humans ( Figure 3 ). Moreover, these studies support the possible role of the gut microbiome in the modulation of brain tumor immunosuppression.…”
Section: Gut Microbiome and Gliomamentioning
confidence: 72%
“…A potential relationship between intestinal flora and malignant brain tumors has been revealed. Lyu Y et al and D’Alessandro G et al observed that by influencing the immune system and modulating neurotransmitters, the crosstalk between intestinal flora and the brain could lead to the formation and development of gliomas [ 14 , 15 ]. This hypothesis was validated by Patrizz A et al [ 16 ] and Xiaochong L et al [ 17 ] in rat experiments, while a human study by Yuqi W [ 18 ] proved that oral microbiota is associated with the malignancy of brain tumors.…”
Section: Introductionmentioning
confidence: 99%